Effect of Body Fat and BMI on Muscle Strength and Endurance in Young Adults: A Cross-sectional Study - Dipak Kumar Dhar; Brijesh Purwar (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Muscle strength and endurance are key determinants of physical fitness, cardiometabolic profile, and overall health. Clinically, they are tested by estimating Handgrip Strength (HGS) and Handgrip Endurance (HGE) through an isometric contraction of the flexors of the forearm and hand. Body Mass Index (BMI) and body fat content can both influence muscle performance, but there are wide variations regarding their effects. BMI and body fat also do not show unequivocal similarity to each other. Aim: The aim of this study was to determine and compare the effects of BMI and body fat on muscle strength and endurance. Materials and Methods: A descriptive cross-sectional study was conducted at the Department of Physiology, Himalayan Institute of Medical Sciences, Swami Rama Himalayan University, Jolly Grant, Dehradun from April 2019 to March 2020. A total of 100 subjects who fulfilled the selection criteria were included. BMI and body fat were measured, and HGS and HGE were recorded using a handgrip dynamometer. Statistical analysis was performed using SPSS version 17.0. Descriptive statistics, independent sample t-test, and one-way ANOVA were used for comparison. Pearson’s correlation coefficient and linear regression were used to determine and quantify the nature of the effect, with a p-value of ≤0.05 considered statistically significant. Results: The participants had a mean BMI of 23.809±3.798 kg/ m2 and a mean body fat percentage of 25.309±7.162%. The mean HGS and HGE of the participants were 36.08±9.956 kg and 18.46±14.2 seconds, respectively. Body fat percentage showed a negative and moderately significant correlation (p-value≤0.001) with both muscle strength and endurance. Approximately one-fifth of the variations in muscle strength and one-third of the variations in muscle endurance were determined by body fat content. HGS and HGE were higher in males, while body fat percentage was higher in females. Gender variation in body fat contributed to more than 40% of the variance. Conclusion: The study revealed a negative correlation between total body fat and muscle strength and performance. Keeping body fat under control can improve muscle performance, which, in turn, enhances cardiometabolic health.